Papyrus PM 49.11.1, Dating the Great Tomb Robberies, and the Chronology of the Late 20th Dynasty - Antoine, Jean-Christophe (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The Great Tomb Robbery papyri are a major source of information on the end of the 20 th Dynasty. Questioned in year 1 of the Renaissance thieves mention the taking of Medinet Habu by foreign troops, an attack of Hardai in Middle Egypt by the Viceroy of Kush Panehsi, and a temporary destitution of the High Priest of Amun (HPA), that are unfortunately not dated. The way forward to resolve this uncertainty is to date the thefts themselves since they were contemporaneous. For this we systematically reviewed what we know of the prosopography of the people involved in the thefts and their investigation. The result shows that tombs and temples robberies mostly occurred between the end of the reign of Ramesses IX and the early years of Ramesses XI. In addition, P. PM 49.11.1 mentions an otherwise unattested HPA Nesmut. The consequences of these results on the history of this period are discussed.